Deep sea squid in Sulawesi Sea, North Sulawesi Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pratasik SB, Lalamentik LTHX, Manoppo L, Budiman J. 2022. Deep sea squid in Sulawesi Sea, North Sulawesi Province, Indonesia. Biodiversitas 23: 1774-1779. This study aimed to identify one of the deep sea squids caught in artisanal fisheries by traditional fishermen in Sulawesi Sea, North Sulawesi Province, Indonesia. Samples were collected using the vertical hand line of traditional fishermen. The specimen was identified using Cytochrome c oxidase subunit 1 (CO1). For morphometric characteristics, all body parts were measured, and each part was compared with mantle size. Results showed that the specimen was identified as purpleback flying squid Sthenoteuthis oualaniensis and had 99.35% similarity to S. oualaniensis (CO1) from China (NCBI - MN101944) with sufficient genetic diversity. Based on the body size, species recorded in the present study belong to the dwarf form, the smallest form of S. oualaniensis groups. The species has the following morphometric characteristics: Head length is 0.28 of mantle length, tentacle length is 1.158 of mantle length, and fin area is 0.5 of mantle length. The fourth arm is the shortest and the second arm is the longest. S. oualaniensis recorded in the present study belonged to dwarf form living in equatorial waters. This finding may contribute to the list of marine resources of fisheries in Indonesian waters.
Keywords: CO1 gene, hand line, morphometric, species identification, traditional fishermen